HUBUNGAN ANTARA TINGKAT EKONOMI KELUARGA DENGAN STATUS GIZI BALITA DI DESA CANDIHARJO KECAMATAN NGORO KABUPATEN MOJOKERTO - Fatimah, Siti; Jannah, Evilia Fahrotul; Kurniawan, Vendi Eko (WELL BEING, 2018)
Nutritional status is an expression of a state of the equilibrium in the form of specific variables or embodiment of nutrients in the form of specific variables. This study design is the design of analytic correlation study with cross sectional approach.The population in this study 32 respondents, with a total sample of 32 respondents using simple random sampling are technique. Measuring instruments used are questionnaires and observation KMS. The result showed the economy is of respondents and good nutritional status is almost entirely 11 (84.6%) of respondents. From the analysis shows the correlation was r = 0.436 and ρ = 0.013 meaning <value ɑ = 0.05, so that there is a relationship between economic level of families with nutritional status of children in the village Candiharjo District of Ngoro Mojokerto. To improve the nutritional quality of the people and mothers with toddlers should actively following nutritional counseling. And the role of health workers or the public in monitoring the development of the nutritional status of children, as well as obtaining information from books and the media.